Antioxidant and Thrombolytic Activities of Methanolic Extracts of Achyranthes aspera Linn. - Raut, B.; Khanal, D.P.; Bhandari, K. (Journal of Manmohan Memorial Institute of Health Sciences, 2021)
Background: Plants have been used since a long time for the therapeutic use and precursors of therapeutic agents. People depend upon the herbal and traditional medicine to satisfy their health care needs. Achyranthes aspera L. is a multifunctional plant used to treat various kinds of diseases. It possesses various type of activities such as antioxidant, anti-inflammatory, antimicrobial and thrombolytic activity. Study of various biological activities helps to provide evidence to the traditional knowledge. Therefore, antioxidant and thrombolytic activities of its stem-leaves were aimed to explore in the present study. Methods: Quantitative experimental method was applied to its antioxidant and thrombolytic activities. Stem-leaves of Achyranthes aspera collected from Thankot, Kathmandu was subjected for methanolic extraction by maceration method. The extract was screened for the antioxidant activity by using DPPH radical scavenging assay as well as thrombolytic activity through the clot lysis assay in human blood. Results: The methanolic extractive value by using maceration was found to be 6.12%. Extract showed their antioxidant and thrombolytic potentialities. The concentration of antioxidants needed to decrease the initial DPPH concentration by 50% (IC50) was found to be 30.5μg/ml for its extract and it was almost 5-fold lesser than ascorbic acid, 6.62 μg/ml. Similarly, the% clot lysis was found to be 7.29 % and 15.35 % in 10 mg/ml and 25 mg/ml concentration respectively. Conclusion: The study suggests that stem-leaves of Achyranthes asperaare the possible sources of natural radical scavenger as well as thrombolytic agents. Thus, they could be used as natural antioxidants as well antithrombosis in the beverage, functional food and pharmaceutical industries that need further wide range in vivo studies.